2020
DOI: 10.1021/acs.nanolett.0c00313
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Templated Timer Probes for Multiplexed Sensing

Abstract: Simultaneous analysis based on encoded fluorophores suffers from potential crosstalk between fluorophores and the limited number of colors that can be practically resolved. Inspired by nontrivial temporal patterns in living organisms, we developed a DNA-templated probe by utilizing DNA polymerase (DNAP) for multiplexed detection of nucleic acids. These probes use differential delay times of signaling by a DNAP-mediated extension to distinguish different targets, which serve as the primers. Taking advantage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
1
12
2
Order By: Relevance
“…These polymerization rates are consistent with the ones measured by Deng et al. who also found that the rate increases with temperature [32] …”
Section: Resultssupporting
confidence: 92%
“…These polymerization rates are consistent with the ones measured by Deng et al. who also found that the rate increases with temperature [32] …”
Section: Resultssupporting
confidence: 92%
“…These polymerization rates are consistent with the ones measured by Deng et al who also found that the rate increases with temperature. [32] Despite an overall good agreement, the measured rates for long binding domains are higher than our predicted…”
Section: Per Rate Dependency On Binding Domain Lengthcontrasting
confidence: 59%
“…The only unknown parameter in the model is k 2 , the polymerization rate of Bst Large Fragment Polymerase, which Deng et al measured to be around 10 À 3 s À 1 . [32] Using these input parameters, Equation (3) predicts that the reaction rate is maximal for 10-nucleotide primers at 25 °C and for 12-nucleotide primers at 37 °C and that shorter or longer primers lead to slower reactions.…”
Section: Per Rate Dependency On Binding Domain Lengthmentioning
confidence: 99%
“…In these experiments, we observed that decaging rates were positively correlated to both pH and temperature. Excitingly, this provides a tunable deprotection rate in a variety of assay conditions and highlights the potential of glyoxal caging for constructing programmable nucleic acid–based clocks, thermometers, and pH-responsive elements in nanodevices and biological circuits. We also assessed room temperature stability of glyoxal adducts and observed minimal decaging over several days, indicating that glycation is stable in practical laboratory conditions until deprotection is triggered by elevated temperatures at the desired time (Figure S5). Although these PAGE experiments provide only a qualitative analysis our model DNA strand, they also illustrate a general kinetic framework of glyoxal caging and decaging.…”
Section: Resultsmentioning
confidence: 86%